The concept of space in the Book of Judith: a contribution to the narrative analysis of Old Testament texts - Korytiaková, Martina (The Septuagint in its ancient context, 2024)
"In the last decade, biblical exegesis has gradually taken into consideration the so-called "spatial turn." However, the literary concept of space and its narrative analysis have found less interest than the study of space as a social and cultural phenomenon. This obvious gap in biblical research has become the impulse for the present work, dedicated to the book of Judith. Its aim is, on the one hand, to present the narrative analysis of space as a still-developing field in non-biblical literature and, on the other, to show how this promising approach can be developed in biblical studies. In particular, this monograph provides the narrative analysis and interpretation of space in the book of Judith in response. The first part of the study offers a synthetic overview of perceptions, concepts and theories of space from antiquity to contemporary research, and of the theoretical approaches to space in the Old Testament. The main part is dedicated to the analysis of space on the micro and macro levels of the Judith story through the application of Katrin Dennerlein's narratological theory of space. Thus, it can be demonstrated to what extent an in-depth analysis of the notion of space can contribute to better understand its thematic and symbolic dimension in the narrative, its function of characterising persons and actions, its role as a structuring element in the story and, last but not least, as a vehicle for an ideological and theological message."